Albumin–Indocyanine Green Evaluation (ALICE) grade combined with portal hypertension to predict post‐hepatectomy liver failure. Issue 8 (7th April 2019) - Shirata, Chikara; Kokudo, Takashi; Arita, Junichi; Akamatsu, Nobuhisa; Kaneko, Junichi; Sakamoto, Yoshihiro; Kokudo, Norihiro; Hasegawa, Kiyoshi
Abstract : Aim: The aim of this study was to evaluate the role of liver function factors in predicting a postoperative large‐volume ascites (LA) and post‐hepatectomy liver failure (PHLF). Methods: We included 1025 consecutive patients undergoing hepatectomy for hepatocellular carcinoma between 2002 and 2014. Univariate and multivariate analyses were carried out to evaluate the role of each factor of liver function in predicting LA and PHLF. Factors included the presence of portal hypertension (PH), extent of resection, Model for End‐stage Liver Disease (MELD) score, and Albumin–Indocyanine Green Evaluation (ALICE) grade. Results: The ALICE score was the strongest predictor for LA (odds ratio [OR], 5.02) and PHLF (OR, 10.94). Conversely, MELD score was not a significant predictive factor for LA or PHLF based on the multivariate analysis. In the ALICE grade 2 group, patients with PH showed a significantly high incidence of developing LA and experiencing PHLF compared with those without PH (LA, 22.4% vs. 10.3%, P  < 0.001; PHLF, 8.6% vs. 1.3%, P < 0.001, respectively). Of patients in the ALICE 2 group, those undergoing sectoriectomy or more extensive resection were associated with extremely poor outcomes (LA, 54.2%; PHLF, 29.2%). Conclusions: A combination of ALICE grade and presence of PH is a useful predictor of LA and PHLF.